Draft Tenth Five Year Plan 2002-2007 & Annual Plan 2002-2003 Volume-III - Planning Commission (Planning Commission, 2002)
Draft tenth plan (2002-2007) and draft annual plan 2002-2003 proposed outlay (gn - statement) draft tenth plan 2002-07 and annual plan 2002-03 - proposed outlay physical target and achievement (general) summary statement draft tenth plan (2002 - 2007) proposals for programmes/ projects statement regarding extemahv aided projects draft tenth plan (2002-07) and draft annual plan (2002-03) outlays - by heads of development for district plans centrally sponsored schemes (css) centrally sponsored scheme ( hill areas) draft tenth plan 20022007 and draft annual plan 20022003 pradhan mantr grammodaya yojana outlay/ expendture
Planning and Development Department Government of Assam